Impact of Toxic Leadership on Employee Performance - Christian Wiradendi Wolor; Ardiansyah Ardiansyah; Rofi Rofaida; Ahmad Nurkhin; Mahmoud Ali Rababah (Health Psychology Research)
This research intends to shed additional light on the effects of toxic leadership on employee satisfaction, motivation, and performance. Such a study on toxic leadership is required since, to date, no research in Indonesia have sought to quantify the consequences of toxic leadership on organizational leaders. Using surveys and structural equation modeling, a quantitative strategy was adopted (SEM). The research sample amounted to 400 taken from 8 locations in Indonesia. Using Google Forms, questionnaires were distributed to 400 employees and analyzed using the Lisrel 8.5 program. The results show that toxic leadership has an effect on job satisfaction (p > 0.00), toxic leadership has an effect on work motivation (p > 0.00), toxic leadership has no effect on employee performance (p < 0.00), job satisfaction has an effect on work motivation (p > 0.00), job satisfaction has effect on employee performance (p > 0.00) work motivation has no effect on employee performance (p < 0.00). The consequences of the study findings for organizations range from the process of screening and selection of leaders to creating stress management and self-resilience training to help employees deal with their emotions in healthy ways and strengthen their defenses.